Diagnostic Test Fine Needle Aspiration Biopsy (FNAB) Examination on Gold Standard Histopathological Tests for Identification of Colli Lymphadenopathy Patients at RSPAL. Dr. Ramelan Surabaya - Devan Andhika; Anik Handayati; Evy Diah Woelansari (International Journal of Advanced Health Science and Technology, 2023)
Lymphadenopathy is a common clinical manifestation which requires rapid and accurate diagnosis. Fine Needle Aspiration Biopsy (FNAB) is used as an initial and direct diagnosis in cases of lymphadenopathy, confirmatory diagnosis of colli lymphadenopathy is carried out by histopathological examination. The purpose of this study was to determine the value of the FNAB diagnostic test for lymphadenopathy colli FNAB against the gold standard histopathology of Paraffin Blok for benign and malignant lymphadenopathy, examination data for Colli Lymphadenopathy obtained at RSPAL has never been studied before. This type of research is observational descriptive by taking medical record data (SIM-RS) of patients with lymphadenopathy in the colli region who were examined for FNAB and histopathology at the Anatomical Pathology Laboratory Installation, RSPAL dr. Ramelan Surabaya for the period January 2019 – March 2022. The sample used was selected using the total sampling method, obtained as many as 66 samples that met the inclusion criteria. The results of the FNAB examination were then matched against the histopathological gold standard examination data. Furthermore, the data was processed by 2x2 crosstabulation and diagnostic tests were carried out to determine the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy. The results showed that the accuracy of the FNAB diagnostic test was 86.56%, sensitivity 80.48%, specificity 96.15%, positive predictive value 97.05%, negative predictive value 75.75%. In general, it can be stated that the FNAB examination can be a screening diagnostic tool that is easy, fast, relatively affordable and applicable in helping to establish the diagnosis of colli lymphadenopathy.